Analysis of Islamic Family Education: Perspective of Surah Ali Imron: 33 – 37 - Arif Efendi (Kirana Publisher (KNPub), 2023)
The smallest group of people receives their primary education from their families. The purpose of the study is to determine how Imron's family's education served as an example for humanity. research using a qualitative approach and a descriptive methodology. approaches for data collection employing studies of both classical and contemporary literature. The investigation discovered that Ali Imron's letter 33–37 described family education in the following ways: A. The realm of direct educators Allah swt, the Messenger of Allah saw, Prophet Imron and wife, Maryam, and prophets Isa As and Ayyub AsB People in general and Muslims, particularly Imron and Maryam, Prophet Ayyub As, and Prophet Isa As, are the proteges. He received an education in tawhid, worshid, morals, psychology, and family education through the use of materials. D. The best ways to instruct directly, give advice, practice in the field, and pray. The smallest community group's primary form of education is provided by their families. The purpose of the study is to determine how Imron's family's education becomes a paradigm for humanity. The study employs a descriptive methodology with a qualitative approach, collecting data utilizing sources from both ancient and contemporary literature. According to the study, family education in Ali Imron's letters from 33 to 37 is as follows: a. The realm of Allah swt's direct educators includes the Prophet Imron and his wife Maryam, the Prophet Isa As, and the Prophet Ayyub. b. In general, students are people, particularly Muslims like Imron and Maryam, the prophet Ayyub, and the prophet iIsa As. c. Monotheism education, worship, morals, psychology, and family are the subjects being taught.